PSXVI-24 Effects of sericea lespedeza on parasite load and oxidative stress in mature horses. (7th December 2018) - Fagan, M; Blackwell, M; Swint, C; Britt, A; Duberstein, K
Abstract: Parasite control in the equine industry is primarily accomplished through deworming programs that implement anthelmintics. The dominant equine parasite of concern is cyathostomins which have the unique ability to encyst in the gut wall while conditions are unfavorable for survival, leading to significant anthelmintic resistance. Similar resistance seen in small ruminants has led to research centered around non-chemical parasite control that involves feeding Sericea lespedeza (SL), a legume high in condensed tannins (CT). In addition to an anthelmintic effect, CTs may enhance antioxidant capacities to combat oxidative stress in inflammatory processes. This two phase preliminary study aimed to (1) determine the effects of SL vs Russell bermudagrass (RB) with regards to short-term parasite load in horses and (2) determine the effects of SL on oxidative stress in response to a single exercise bout. Data was analyzed using SAS version 9.4. Phase one consisted of 16 horses divided into two groups for 4wks and fed daily 1.5% bodyweight (BW) of SL or RB. Fecal egg counts (FEC) were performed on days 0, 14, 28 and 42. There was no statistical difference between FEC of treatment groups at d0, d28 or d42 (P>0.05), however a statistical difference was seen between treatment groups in horses with FEC0.05). In conclusion, short term feeding of SL did not decrease parasite load or improve antioxidant capacity in response to a single exercise bout. Future studies may consider the efficacy of SL over a longer feeding or training period.